Extremely Stable Platinum Nanoparticles Encapsulated in a Zirconia Nanocage by Area‐Selective Atomic Layer Deposition for the Oxygen Reduction Reaction. (18th November 2014) - Cheng, Niancai; Banis, Mohammad Norouzi; Liu, Jian; Riese, Adam; Li, Xia; Li, Ruying; Ye, Siyu; Knights, Shanna; Sun, Xueliang
<x xml:space="preserve">Abstract</x> Encapsulation of Pt nanoparticles (NPs) in a zirconia nanocage by area‐selective atomic layer deposition (ALD) can significantly enhance both the Pt stability and activity. Such encapsulated Pt NPs show 10 times more stability than commercial Pt/C catalysts and an oxygen reduction reaction (ORR) activity 6.4 times greater than that of Pt/C. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>